2022
DOI: 10.3233/jad-220170
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depressive Symptoms in a Memory Clinic Cohort: A Retrospective Study

Abstract: Background: Depression has been suggested to be a cause of reversible cognitive impairment but also a risk factor for neurodegenerative disease. Studies suggest that depression prevalence may be high in early onset dementia, particularly Alzheimer’s disease, but this has not been systematically assessed in a biomarker-validated clinical dementia cohort to date. Objective: To examine the prevalence, features, and association with amyloid pathology of lifetime depressive symptoms in a memory clinic cohort meetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Comorbid depressive symptoms are a frequent feature in patients with AD 8 , but the nature of this link is still unclear. Where possible (n=83), we classified patients according to whether they had past (n=7), ongoing (n=24), or no (n=51) depressive symptoms at the time of presentation to our clinic (see Loreto et al, 2022 for classification procedure).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Comorbid depressive symptoms are a frequent feature in patients with AD 8 , but the nature of this link is still unclear. Where possible (n=83), we classified patients according to whether they had past (n=7), ongoing (n=24), or no (n=51) depressive symptoms at the time of presentation to our clinic (see Loreto et al, 2022 for classification procedure).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, research into its earlier phases has highlighted that AD is a continuum, rather than a discrete clinical entity, that goes from normal cognitive status to mild cognitive impairment to dementia 2 3 . Moreover, AD often coexists with other neuropathologies 4 or clinical comorbidities 5-8 that contribute to interindividual heterogeneity. In a recent study evaluating a memory clinic cohort, we have found that about half of patients requiring biomarker confirmation of AD due to diagnostic uncertainty also reported depressive symptoms 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All 77 patients included in this study were scanned using a Siemens Biograph 64 PET/CT scanner. The amyloid PET procedure and clinical interpretation were performed as described elsewhere 36,37 . Briefly, images were acquired following post‐injection interval of intravenous 18F‐Florbetapir or 18F‐Florbetaben and were visually read as positive or negative by an experienced nuclear medicine radiologist.…”
Section: Methodsmentioning
confidence: 99%
“…The impact of a diagnosis of Alzheimer’s disease (AD) is one of the most devastating stressful life events at the end of life. Depending on the premorbid psychopathological situation of patients, especially that related to mood disorders, comorbid disorders that accelerate cognitive, functional, and structural deterioration in frontotemporal brain areas are to be expected [ 1–3 ].…”
Section: Introductionmentioning
confidence: 99%